EPIDEMIOLOGICAL CHARACTERISTICS OF VIRAL HEPATITIS IN PATIENTS WITH RHEUMATIC DISEASES - IMPLICATIONS FROM TREASURE DATABASE - Ersozlu, D.; Ekici, M.; Coskun, B. N.; Badak, S. O.; Bilgin, E.; Kalyoncu, U.; Ertenli, A. I. (Elsevier, 2022)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 01-04, 2022 -- Copenhagen, DENMARK